The Role of Informed Consent as An Instrument of Legal Protection in Dental Services: A Comparative Literature Study in Indonesia - Agung Bagus Swamadi; Ary Natalia Yuda (Indonesian Journal of Global Health Research, 2026)
Informed consent is a fundamental ethical and legal requirement in healthcare that safeguards patient autonomy while protecting healthcare professionals from legal disputes. In dental practice, informed consent extends beyond obtaining a patient's signature, encompassing a comprehensive communication process that enables patients to make informed decisions regarding diagnosis, treatment alternatives, benefits, risks, and possible complications. Despite recent regulatory reforms through Law Number 17 of 2023 concerning Health and Government Regulation Number 28 of 2024, challenges remain in the consistent implementation of informed consent within Indonesian dental services. This study aimed to comprehensively review the role of informed consent as an instrument of legal protection for dentists in Indonesia by comparing existing scientific evidence with the current national legal framework governing dental practice. A systematic literature review employing a comparative legal approach was conducted following the PRISMA 2020 guidelines. Literature was retrieved from PubMed, Scopus, ScienceDirect, and Google Scholar using Medical Subject Headings (MeSH) and free-text keywords related to informed consent, dentistry, legal protection, and health law. Eligible studies addressing legal, ethical, and clinical aspects of informed consent in dental services were selected according to predefined inclusion and exclusion criteria. Relevant Indonesian legislation, including Law Number 17 of 2023 and Government Regulation Number 28 of 2024, was also analyzed. Extracted data were synthesized using qualitative thematic analysis. The review demonstrates that informed consent functions as both an ethical obligation and a legal safeguard by promoting patient autonomy, supporting shared decision-making, and providing documentary evidence of professional compliance. Medical records and informed consent collectively strengthen legal protection for dentists by documenting adherence to professional standards and reducing medico-legal risks. Nevertheless, implementation in Indonesian primary healthcare facilities remains constrained by high patient workloads, limited human resources, inconsistent documentation practices, inadequate digital infrastructure, and insufficient understanding of medico-legal responsibilities among healthcare professionals. Effective implementation of informed consent requires integration of comprehensive documentation, standardized operating procedures, continuous legal and ethical education, and strengthened electronic medical record systems. Harmonizing clinical practice with Indonesia's evolving legal framework will improve patient safety, reinforce professional accountability, and enhance legal protection for dentists delivering dental healthcare services.